Dietary composition of the silvery gibbon (Hylobates moloch) in the Northwestern Dieng Mountains, Indonesia using fecal metabarcoding and field surveys - TRI SETIA KURNIA NURI; SURATMAN SURATMAN; ARI SUSILOWATI; PUGUH KARYANTO (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Nuri TSK, Suratman, Susilowati A, Karyanto P. 2026. Dietary composition of the silvery gibbon (Hylobates moloch) in the Northwestern Dieng Mountains, Indonesia using fecal metabarcoding and field surveys. Biodiversitas 27 (4): d270443. https://doi.org/10.13057/biodiv/d270443. Forest degradation has altered vegetation structure and composition, affecting the silvery gibbon's ability to adapt to fluctuating food availability. Understanding these adaptations provides essential baseline information for assessing population viability. We tested the hypothesis that Hylobates moloch exhibits dietary selectivity by comparing plant abundance in fecal metabarcoding data against vegetation metrics from field surveys, including species richness and the Importance Value Index (IVI). Additionally, we evaluated whether metabarcoding provides a broader dietary profile than traditional ground-based methods. We employed rbcL-based Next-Generation Sequencing (NGS) on five pooled fecal samples collected during the early dry season, complemented by the Point-Centered Quarter (PCQ) method and ethnobiological interviews. NGS analysis yielded 13,040 Amplicon Sequence Variants (ASVs), representing 28 orders, 47 families, 64 genera, and 29 species. Of these 47 families, 40.43% (19 families) were fully corroborated by both PCQ vegetation surveys and local interviews, underscoring the strong complementarity of these techniques. While the survey identified more than 40% tree species, the NGS data revealed a more specialized dietary niche. Field surveys effectively captured essential canopy food sources, whereas metabarcoding complemented these findings by identifying non-woody, rare, and understory taxa typically excluded from conventional tree plots. The three most abundant taxa based on Relative Read Abundance (RRA), Ficus benjamina, family Moraceae, and Gnetum spp., were identified as primary dietary components. Our findings yielded vital dietary data underscoring a practical conservation plan for Javan gibbons. We confirm that H. moloch selectively forages on specific taxa, with Moraceae serving as the predominant food source during the early dry season. Consequently, long-term conservation should prioritize restoring key fruit taxa and maintaining forest diversity to ensure their survival.